2018
DOI: 10.5154/r.rchscfa.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de cuatro bosques de pino piñonero del estado de Zacatecas, México

Abstract: Introducción: Las comunidades dominadas en el dosel por los pinos piñoneros albergan riqueza de especies y presentan fisionomía compleja, debido a que forman un ecotono entre zonas áridas y templadas.Objetivos: Describir los atributos florísticos que distinguen a cuatro comunidades dominadas por pinos piñoneros; definir unidades con base en la composición florística y estructura; y determinar la influencia de los factores edáficos.Materiales y métodos: Se registró la flora de cuatro comunidades en el estado de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
1
3
0
7
Order By: Relevance
“…Specifically, for the Susticacán oak forests, their structure and composition, as well as their establishment on slopes with less solar exposure and a notably less arid climate, are consistent with those reported for this type of vegetation in the SMOc by Granados-Sánchez et al [59] and González-Elizondo et al [46], as well as for the oak forests of the state of Zacatecas by Sabas-Rosales [58]. Regarding pine forests, Barrera-Zubiaga et al [60] reported this type of vegetation occurring in the central (Fresnillo), northeastern (Concepción del Oro), and north-western (Sombrerete) parts of Zacatecas; however, there was no formal record for Susticacán, located in the central-western part of the state. In this last plant community, the presence, albeit in low frequency, of Dodonaea viscosa, constitutes a potential threat to the native flora, since it has been reported to replace the oak and pineoak forests of the SMOc [61].…”
Section: Discussionsupporting
confidence: 83%
“…Specifically, for the Susticacán oak forests, their structure and composition, as well as their establishment on slopes with less solar exposure and a notably less arid climate, are consistent with those reported for this type of vegetation in the SMOc by Granados-Sánchez et al [59] and González-Elizondo et al [46], as well as for the oak forests of the state of Zacatecas by Sabas-Rosales [58]. Regarding pine forests, Barrera-Zubiaga et al [60] reported this type of vegetation occurring in the central (Fresnillo), northeastern (Concepción del Oro), and north-western (Sombrerete) parts of Zacatecas; however, there was no formal record for Susticacán, located in the central-western part of the state. In this last plant community, the presence, albeit in low frequency, of Dodonaea viscosa, constitutes a potential threat to the native flora, since it has been reported to replace the oak and pineoak forests of the SMOc [61].…”
Section: Discussionsupporting
confidence: 83%
“…Floristic composition was derived from floristic listings of the following studies: Hernández and García (1985); Suzán-Azpiri and Galarza (1987); Reyes-Agüero, González-Medrano, and García-Pérez (1996); Granados-Sánchez and Sánchez-González (2003); González, Giménez, García, and Aguirre (2007); Villarreal, Mares, Cornejo, and Capó (2009); Giménez and González (2011); Romero et al (2014); Torres-Colín et al (2017), and De-Nova, Castillo-Lara, Gudiño-Cano, and García-Pérez (2018). Species related to pinyon pine forests were selected and seasonal collections were made from September 2019 to March 2021 using the floristic sweep method (Barrera-Zubiaga et al, 2018) which consisted of walks, collection of specimens and herborization, for…”
Section: Floristic Compositionmentioning
confidence: 99%
“…Pinyon pine forests provide a variety of environmental services (Reyes-Carrera, Méndez-González, Nájera-Luna, & Cerano-Paredes, 2013) through the production of pinyon nuts, firewood and other non-timber forest products that are essential to the local economy; however, excessive resource overexploitation, especially intensive pinyon nuts harvesting and overgrazing, have caused the decline of these communities, drastically reducing their extent and diversity (Barrera-Zubiaga, Granados-Sánchez, Granados-Victorino, & Luna-Cavazos, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, los valores de altura del bosque de Quercus-Pinus son similares a los bosques de Pinus cembroides Zucc. de Zacatecas (4.25±3.09 m) (Barrera-Zubiaga et al, 2018) que, por su cercanía, pueden tener condiciones ambientes y de sitio muy similares. En este anterior caso se contemplaron especies tanto arbóreas como arbustivas.…”
Section: Estructuraunclassified